Image-based in vitro screening reveals the trypanostatic activity of hydroxymethylnitrofurazone against trypanosoma cruzi - Scarim, Cauê Benito [UNESP]; Olmo, Francisco; Ferreira, Elizabeth Igne; Chin, Chung Man [UNESP]; Kelly, John M.; Fortes Francisco, Amanda (MDPI, 2021)
Hydroxymethylnitrofurazone (NFOH) is a therapeutic candidate for Chagas disease (CD). It has negligible hepatotoxicity in a murine model compared to the front-line drug benznidazole (BZN). Here, using Trypanosoma cruzi strains that express bioluminescent and/or fluorescent reporter proteins, we further investigated the in vitro and in vivo activity of NFOH to define whether the compound is trypanocidal or trypanostatic. The in vitro activity was assessed by exploiting the fluorescent reporter strain using wash-out assays and real-time microscopy. For animal experi-mentation, BALB/c mice were inoculated with the bioluminescent reporter strain and assessed by highly sensitive in vivo and ex vivo imaging. Cyclophosphamide treatment was used to promote parasite relapse in the chronic stage of infection. Our data show that NFOH acts by a trypanostatic mechanism, and that it is more active than BZN in vitro against the infectious trypomastigote form of Trypanosoma cruzi. We also found that it is more effective at curing experimental infections in the chronic stage, compared with the acute stage, a feature that it shares with BZN. Therefore, given its reduced toxicity, enhanced anti-trypomastigote activity, and curative properties, NFOH can be considered as a potential therapeutic option for Chagas disease, perhaps in combination with other trypanocidal agents.
Keywords: Benznidazole; Bioluminescence imaging; Chagas disease; Hydroxymethylnitrofura-zone; Trypanosoma cruzi; Trypanostatic effect